Hepatoprotective effect of hydroalcoholic extract from root of Sechium edule (Jacq.) Sw. over hepatic injury induced by chronic application of angiotensin II - Alvarado-Ojeda, Zimri Aziel; Coset Mejia, Alejandro; Arrellin Rosas, Gerardo; Jiménez-Ferrer, Jesús Enrique; Zamilpa, Alejandro; Trejo-Moreno, Celeste; Castro Martínez, Gabriela; Méndez Martínez, Marisol; Cervantes Torres, Jacquelynne; Báez Reyes, Juan Carlos; Fragoso, Gladis; Rosas Salgado, Gabriela (Frontiers in Natural Products, 2022)
Liver damage is characterized by lipid accumulation in the liver, a prooxidant/proinflammatory state, necrosis, and fibrosis. Given the multifactorial conditions and complexity of the disease and the contribution of oxidative stress and inflammation in its development, phytomedicine is a good option for its control. Liver damage was induced in male C57BL/6J mice by chronic administration of angiotensin II (ANGII) (0.01 μg/kg/day, administered daily intraperitoneally). A hydroalcoholic extract of Sechium edule root (rSe-HA), standardized for its cinnamic acid content, was used to control the incidence of liver damage in mice (11 mg/kg/day of rSe-HA, administered orally). After 11 weeks, the mice were sacrificed and adipose tissue, serum, and liver were obtained. Hepatic cytokine and triglyceride (TG) concentrations were determined, and any histopathological changes were recorded. Meanwhile, ANGII treatment increased serum TG concentration (62.8%), alanine aminotransaminase (GPT/ALT) levels (206%), as well as TG accumulation (82.7%), hepatomegaly (32.1%), inflammation (measured by TNFα (70%), IL-1β (103%), IL-6 (92%) and TGFβ (203%) levels, along with inflammatory cell recruitment), and fibrosis with respect to untreated controls. rSe-HA prevented these increases, maintaining all parameters evaluated at values similar to those of the control group. Overall, our results support the hepatoprotective effects of rSe-HA against NAFLD and NASH, which are often the gateway to more severe pathologies